Legal Protection for Land Rights Holders Included in the Toll Road Development Project Plan Accompanied with Compensation - Adhie Charisma, Restu; Anriz Nazaruddin Halim; Taqiyuddin Kadir (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
One of the issues that currently arises is related to the fulfillment of community needs in the concept of social functions, namely land acquisition for development in the public interest. On the other hand, land rights holders whose land will be used for development in the public interest should not be disadvantaged and ruled out at all. To support this, the government provides a legal basis so that the release of land rights used for the public interest must also pay attention to the aspect of balanced compensation. The formulation of the problem in this study, How is the settlement of disputes over the construction of toll roads on the value of compensation to land rights holders and How is the Legal Protection of land rights holders related to compensation disputes in toll road construction projects, the theory used in this study is the Theory of Legal Protection, according to Philipus M. Hadjon and the theory of dispute resolution according to Yahya Harahap. The method used in the research, namely, normative juridical research, namely library legal research or secondary data with primary, secondary and tertiary legal sources. The approach in this research is, namely, the approach of legislation, conceptual approach and case approach and the technique of collecting legal materials is done by means of document studies or library materials, observation or observation and interviews or interviews. For legal material analysis techniques carried out by Grammatical, Systematic, and Legal Construction Interpretation. Research results show that the settlement of toll road construction disputes over the value of compensation to land rights holders can only be done through judicial institutions that have an independent nature. Settlement of land acquisition disputes for the public interest must have special material and formal law. Settlement of land acquisition disputes for the public interest cannot be carried out unilaterally only by the government which has equality with land rights holders and legal protection of land rights holders related to compensation disputes in toll road construction projects must be in accordance with applicable law. Land rights are considered as constitutionally protected private property rights. Land is considered as an object that has a closed nature based on laws and regulations.